PERLINDUNGAN HUKUM TERHADAP KONSUMEN ATAS INFORMASI IKLAN PERUMAHAN YANG MENYESATKAN DALAM PERJANJIAN KEPEMILIKAN RUMAH PADA PT. BANGUN PERSADA SEJAHTERA - Setiawan, Budi (Universitas Ekasakti, 2018)
Nowadays the needs of the house are difficult to obtain, although the government is always active and strives to carry out housing development. In the midst of the limited ability of the government, has led to business opportunities to meet the needs of community housing, commonly referred to as developers. Developers in providing homes often do not provide clear information relating to the specification conditions of the house to the consumer. The problems discussed in this thesis writing is, first how the form of legal protection of the consumer for misleading housing ad information? Second, how is the business actor's responsibility for misleading home advertising information? This research is an analytical descriptive research, with normative juridical approach as main approach and empirical juridical as supporter. The data used are secondary data and primary data collected through literature study and field study with interview technique. The analysis is done qualitatively and presented in the form of qualitative descriptive. Based on the results of research that has been analyzed it can be concluded, firstly, forms of legal protection of misleading housing ad information, for the actions undertaken by developers PT. Bangun Persada Sejatera to Villa Anggrek housing consumer, the consumer as an injured party can make various legal efforts to fight for his rights through: the settlement of consumer dispute through litigation and settlement of non-litigation consumer disputes. Secondly, the business actor's responsibility for misleading housing advertising information is that the consumer is entitled to submit his / her complaint relating to the house in the maintenance warranty period of 100 (one hundred) calendar days. Developers as business actors will seek every improvement that complained by consumers. If the consumer feels aggrieved by the business actors, the entrepreneur shall be obliged to provide compensation, compensation and / or reimbursement for loss caused by the user, user and the utilization of the goods and / or services that have been traded.